2006
DOI: 10.1159/000091472
|View full text |Cite
|
Sign up to set email alerts
|

Practical Use of MESNA in Atelectatic Ears and Adhesive Otitis Media

Abstract: Objective: MESNA is a synthetic sulfur compound that produces mucolysis by disrupting disulfide bonds. This study aimed to address indications and technique of MESNA application in otologic surgery, especially in retraction pockets and adhesive otitis media. Methods: MESNA application was performed in 42 ears of 39 patients. The diagnoses were retraction pockets fixed to incudostapedial joint, stapes or promontorium, and adhesive otitis media in 24 and 17 ears, respectively. Calculations were performed accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…Previous studies have reported that the use of MESNA in atelectatic and adhesive middle ear and cholesteatoma surgery is not associated with ototoxic effects and had neuroprotective effects; however, to the best of our knowledge, its direct effect on the facial nerve has not been demonstrated [7][8][9][10]12] . The possibility of dehiscence development in the fallopian canal of the facial nerve is very high in the presence of pathologies progressing with dissolving bone structures, such as cholesteatoma; the use of MESNA for separating the cholesteatoma matrix in such surgeries inevitably results in contact with the facial nerve, directly or by passing through bony dehiscence.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Previous studies have reported that the use of MESNA in atelectatic and adhesive middle ear and cholesteatoma surgery is not associated with ototoxic effects and had neuroprotective effects; however, to the best of our knowledge, its direct effect on the facial nerve has not been demonstrated [7][8][9][10]12] . The possibility of dehiscence development in the fallopian canal of the facial nerve is very high in the presence of pathologies progressing with dissolving bone structures, such as cholesteatoma; the use of MESNA for separating the cholesteatoma matrix in such surgeries inevitably results in contact with the facial nerve, directly or by passing through bony dehiscence.…”
Section: Introductionmentioning
confidence: 79%
“…It is used as a cytoprotective agent to prevent hemorrhagic cystitis and as a mucolytic agent to improve pulmonary functions. In addition, the sulfhydryl group has the potential to clean the reactive oxygen metabolites and is used as a systemic protective agent against chemotherapy toxicity [9,11] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These complications usually occur while performing mechanical dissection of the cholesteatoma matrix from the underlying structures. Yilmaz et al [10] reported that MESNA was successful in atelectatic ears and adhesive otitis media because it made the operation easier and safer by allowing elevation of the tympanic membrane through its mechanical and chemical actions. Kalcioglu et al [14] investigated the use of 20% MESNA in chronic otitis with cholesteatoma and reported that it could be helpful for eliminating the disease and increasing surgical success.…”
Section: Discussionmentioning
confidence: 99%
“…As used in other surgical areas, MESNA can be used during middle ear surgery, such as in the case of cholesteatoma or atelectatic ears, when dissecting the tissue layers [10] . The matrix of cholesteatoma is mainly composed of keratin, a protein rich in disulfide bonds.…”
Section: Introductionmentioning
confidence: 99%